2013
DOI: 10.1016/j.joen.2012.11.026
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxicity Evaluation of a Novel Root Repair Material

Abstract: Introduction: This study examined the effect of a new bioactive dentin substitute material (Biodentine) on the viability of human gingival fibroblasts. Methods: Biodentine, White ProRoot mineral trioxide aggregate (MTA), and glass ionomer cement were evaluated. Human gingival fibroblasts were incubated for 1, 3, and 7 days both in the extracts from immersion of set materials in culture medium and directly on the surface of the set materials immersed in culture medium. Fibroblasts cultured in Dulbecco modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
117
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(152 citation statements)
references
References 33 publications
15
117
1
9
Order By: Relevance
“…Materials that have strong antibacterial properties also tends to have high cytotoxicity (9). The experimental MTA-based material in the present study showed a strong antibacterial effect, but also good low cytotoxicity.…”
Section: Endodontic Filling Materials For Primary Teethsupporting
confidence: 46%
See 1 more Smart Citation
“…Materials that have strong antibacterial properties also tends to have high cytotoxicity (9). The experimental MTA-based material in the present study showed a strong antibacterial effect, but also good low cytotoxicity.…”
Section: Endodontic Filling Materials For Primary Teethsupporting
confidence: 46%
“…Human gingival fibroblasts were obtained from previously established cell line cultured from healthy patients who underwent oral surgery (9). Fibroblasts of the seventh to eighth passage were used in this study.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…It also has a better consistency after mixing and offers ease of placement. 23 Zhou et al 24 have stated that this material can be safely used in procedures requiring close approximation with the periodontal tissue. Two percent chlorhexidine was used as irrigant as it is placed to be more effective against Enterococcus faecalis than sodium hypochlorite.…”
Section: Discussionmentioning
confidence: 99%
“…Some in vitro methods are used to evaluate the toxicity of medical devices standardized by using cell cultures [37][38][39][40]. Methods involving cell cultures can be successfully employed because they are reproducible, fast, sensitive and easy to execute during an in vitro biocompatibility evaluation [41].…”
Section: Methods For In Vitro Cytotoxicity Analysesmentioning
confidence: 99%